ANALISIS DAN PERANCANGAN SISTEM ADMINISTRASI DAN TRANSAKSI BERBASIS CLIENT SERVER - Sofiansyah Fadli; Khairul Imtihan (Jurnal Informatika dan Rekayasa Elektronik, 2018)
Almost all areas of business take advantage of computer technology as a medium of information to obtain information quickly and accurately. Daffa fitnes is one of the fitness centers that have not utilized computer technology, to manage data and provide information for members or visitors who use services on Daffa fitnes. All process activities are done manually, all data written on a plain paper, of course very high risk of loss or damage of data. In the implementation of application systems using Borland Delphi 7 programming for interface design, while for data storage using MySql database and components MyOdbc Connector as a liaison to spread data on server and client computers. It is expected that this system becomes an effective media in the management of administrative data and transactions, with the utilization of client server-based system on the application so as to facilitate the officer in managing the data in accordance with its part. This system is very feasible to be used as a medium to manage data to minimize the occurrence of errors and simplify the maintenance of data.